Why Open Surgical Repair Remains Essential: Insights into the Suitability of Endovascular Aneurysm Repair in Ruptured Abdominal Aortic Aneurysms from a Tertiary Referral Center in South Korea - Kim, Sang Yoon; Yoon, Dong Kyu; Lee, Jae Hang; Chang, Hyoung Woo; Park, Kay-Hyun (Journal of chest surgery, 2025)
Several studies have demonstrated that emergency endovascular aneurysm repair (eEVAR) has become the standard treatment for ruptured abdominal aortic aneurysm (rAAA) compared to open surgical repair (OSR). This study investigated the feasibility of eEVAR in rAAA patients and analyzed the outcomes of OSR. At our institution, all patients (n=58) presenting with rAAA underwent OSR. We conducted a retrospective review of surgically treated rAAA patients between February 2006 and March 2021. Patients with impending rupture or isolated iliac aneurysm rupture were excluded. Anatomic measurements based on preoperative computed tomography indicated that 28 patients (48.3%) could have been candidates for eEVAR. Reasons for unsuitability included: (1) proximal neck length <10 mm (n=21, 51.7%); (2) proximal neck angulation >60° (n=11, 19.0%); (3) iliac artery diameter <5 mm (n=6, 10.3%); and (4) proximal neck diameter >32 mm (n=3, 5.2%). The 30-day mortality rate for OSR was 17.2% (n=10). The 1-year and 5-year survival rates were 53.4%±6.5% and 33.4%±6.3%, respectively. Multivariable logistic regression analysis revealed that a high preoperative serum lactate level (>5 mmol/L) and the presence of bowel ischemia were significant risk factors for 30-day mortality (odds ratio [OR], 11.95; 95% confidence interval [CI], 1.53-93.08; p<0.018; and OR, 15.28; 95% CI, 1.60-146.18; p<0.018, respectively). More than half of rAAA patients were not candidates for eEVAR due to various anatomical reasons. OSR demonstrated favorable short- and long-term outcomes and remains a viable standard treatment for rAAA.